Acceptance of a Malaria Vaccine by caregivers of sick children in Kenya - Ojakaa, David I; Jarvis, Jordan D; Matilu, Mary I; Thiam, Sylla (BioMed Central)
Background Several malaria vaccines are currently in clinical trials and are expected to provide an improved strategy for malaria control. Prior to introduction of a new vaccine, policymakers must consider the socio cultural environment of the region to ensure widespread community approval. This study investigated the acceptance of a malaria vaccine by child caregivers and analysed factors that influence these. Methods Interviews from a standard questionnaire were conducted with 2,003 caregivers at 695 randomly selected health facilities across Kenya during the Kenya Service Provision Assessment Survey 2010. Multinomial regression of quantitative data was conducted using STATA to analyse determinants of caregivers accepting malaria vaccination of their child. Results Mothers represented 90% of caregivers interviewed who brought their child to the health facility, and 77% of caregivers were 20-34 years old. Overall, 88% of respondents indicated that they would accept a malaria vaccine, both for a child in their community and their own child. Approval for a vaccine was highest in malaria-endemic Nyanza Province at 98.9%, and lowest in the seasonal transmission area of North Eastern Province at 23%. Although 94% of respondents who had attended at least some school reported they would accept the vaccine for a child, only 56% of those who had never attended school would do so. The likelihood of accepting one’s own child to be immunized was correlated with province, satisfaction with health care services in the facility attended, age of the caregiver, and level of education. Conclusions Results from this study indicate a need for targeted messages and education on a malaria vaccine, particularly for residents of regions where acceptance is low, older caregivers, and those with low literacy and school-attendance levels. This study provides critical evidence to inform policy for a new malaria vaccine that will support its timely and comprehensive uptake in Kenya
© 2014 Ojakaa et al.; licensee BioMed Central Ltd. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/4.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly credited. The Creative Commons Public Domain Dedication waiver (http://creativecommons.org/publicdomain/zero/1.0/) applies to the data made available in this article, unless otherwise stated.
Keywords: Malaria vaccine; Acceptance; Caregivers; Kenya